COMPARISON OF INTERMODAL TERMINALS IN SLOVAKIA AND CZECH REPUBLIC (Perner's Contacts, 2012)
The paper deals with the analysis of intermodal terminals in various regions of Slovakia and the Czech Republic in terms of selected criteria and then their comparison. Selected criteria include specifically a location, connection, whether they meet the requirements according to the international agreement AGTC in terms of technical equipment, provided services in these objects and their connectivity with surrounding logistics centers.
Keywords: terminals of intermodal transport, bimodality, trimodality, intermodal transport unit, logistics centers